Early outcome of endoscopic mitral valve surgery in elderly patients: a high-volume single center experience - Pausch, Jonas; Bhadra, Oliver D.; Hua, Xiaoqin; Stolfa, Philipp; Kuhlmann, Carolin; Voß, Mirko; Girdauskas, Evaldas; Reichenspurner, Hermann; Conradi, Lenard (Frontiers in Cardiovascular Medicine, 2023)
Objectives Despite increasing use of transcatheter approaches, endoscopic mitral valve surgery (MVS) remains an established option for treatment of mitral regurgitation (MR). Nevertheless, as perioperative risk increases with age, outcome of endoscopic MVS in elderly patients is uncertain. Methods We retrospectively analyzed 756 consecutive patients with MR≥2, who underwent minimally-invasive MVS at our institution between 2016 and 2022. Patients were stratified by age ≥75 (elderly-group; n= 91) or <75 years (control-group; n= 665). All patients received endoscopic MVS via right anterolateral minithoracotomy with non-rib spreading soft tissue retraction and 3D-camera visualization. Results Overall surgical risk was increased in the elderly-group (median age of 77 (76-80) years vs. 58 (51-67) years, p<0.001) with STS-PROM Scores of 1.9% vs. 0.4% (p<0.001) and increased prevalence of hypertension, diabetes, coronary artery disease and atrial fibrillation (AFib). Elderly patients were also more symptomatic (NYHA class III 45.7% vs. 29.8%; p=0.002). Axillo-femoral perfusion was more frequently used in the elderly-group (27.5% vs. 4.2%; p<0.001). Cross-clamp and cardiopulmonary bypass times were similar. Rate of MV repair was 85.7% vs. 93.8% (p=0.005). Closure of the left atrial appendage was more frequently performed in the elderly-group (45.1% vs. 23.9%; p<0.001), whereas rate of concomitant tricuspid valve repair was similar (11.0% vs. 8.9%; p=0.511). Postoperative complications including perioperative hemodialysis (3.3% vs. 2.9%; p=0.739), low cardiac output (5.3% vs. 3.8%; p=0.393), perioperative stroke (1.1% vs. 0.15%; p=0.224) and myocardial infarction (0% vs. 0.15%) were favorably low in both groups. Acute mortality at 30 days was 2.2% vs. 0.4% (p=0.112). Conclusion Despite increased prevalence of outcome-relevant comorbidities and surgical risk, perioperative outcome of patients aged ≥75 years undergoing endoscopic MVS is favorable. Therefore, endoscopic MVS is a valuable therapeutic option for selected elderly patients and should be taken in consideration during routine heart-team discussion.